Novel Loci Underlie Natural Variation in Vitamin E Levels in Maize Grain. Issue 10 (2nd October 2017) - Diepenbrock, Christine H.; Kandianis, Catherine B.; Lipka, Alexander E.; Magallanes-Lundback, Maria; Vaillancourt, Brieanne; Góngora-Castillo, Elsa; Wallace, Jason G.; Cepela, Jason; Mesberg, Alex; Bradbury, Peter J.; Ilut, Daniel C.; Mateos-Hernandez, Maria; et al.
Abstract : This joint linkage and genome-wide association study comprehensively investigates natural variation in maize grain vitamin E levels using the 5000-line U.S. nested association-mapping panel. Abstract: Tocopherols, tocotrienols, and plastochromanols (collectively termed tocochromanols) are lipid-soluble antioxidants synthesized by all plants. Their dietary intake, primarily from seed oils, provides vitamin E and other health benefits. Tocochromanol biosynthesis has been dissected in the dicot Arabidopsis thaliana, which has green, photosynthetic seeds, but our understanding of tocochromanol accumulation in major crops, whose seeds are nonphotosynthetic, remains limited. To understand the genetic control of tocochromanols in grain, we conducted a joint linkage and genome-wide association study in the 5000-line U.S. maize ( Zea mays ) nested association mapping panel. Fifty-two quantitative trait loci for individual and total tocochromanols were identified, and of the 14 resolved to individual genes, six encode novel activities affecting tocochromanols in plants. These include two chlorophyll biosynthetic enzymes that explain the majority of tocopherol variation, which was not predicted given that, like most major cereal crops, maize grain is nonphotosynthetic. This comprehensive assessment of natural variation in vitamin E levels in maize establishes the foundation for improving tocochromanol and vitamin E content in seeds of maize and other major cereal crops.